White people do not know how to behave at entertainments designed for ladies & gentlemen of colour : William Brown's African & American theater - McAllister, Marvin Edward, 1969- (UNC Press law publications., 2003)
An exploration of the career of William Brown, a 19th-century free man of colour, who pioneered theatrical spaces for black New Yorkers, hitherto denied access to whites-only venues. The text explores these intercultural, multiracial environments and investigates negative white reactions.